Ni Una Menos: A rallying cry across history, legislation and the media ([Province of] Neuquén 2015-2023): Ni Una Menos: A rallying cry across history, legislation and the media (Province of Neuquén 2015-2023) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
This article aims to examine the phenomenon Ni Una Menos (“Not One Woman Less” in English), by focusing on three focal points: the history of women’s movements; the development of the legal framework for gender-based violence; and the analysis of the regional media coverage of Ni Una Menos demonstrations and femicides from 2015 to 2023, based on the study of two newspapers: Río Negro and La Mañana de Neuquén. A qualitative gender-centered methodology is adopted, using critical discourse analysis tools. It is highlighted that the historical process led by women’s movements was essential to the recognition of women’s rights, the development of critical discourse and the enactment of new laws. In light of this, Ni Una Menos played a key role in raising awareness about violence against women, and placing the issue at the center of the public and media debate. This article calls into question the role of the regional press on the creation of narratives and construction of meanings around this movement. And while it is pointed out that there have been some improvements on the media coverage of this topic, there are still some media practices that reinforce gender stereotypes, spread fragmented information or depoliticize this issue.